Aplikasi Material Rotan Pada Perancangan Table Lamp - Mawardi, Fayyad Dzaki; Fadlillah , Azly; Ivan, Michael; Dzakwan, Muhammad (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Rattan is one of the main materials in simple crafts and a material for interior furniture items. In Indonesia, rattan is very abundant and is one of the largest rattan producing countries in the world. On the other hand, this rattan material is very popular with furniture entrepreneurs because rattan can be made into creative products that have features both in terms of function and aesthetics.. Furniture produced includes chairs, tables, and decorative products. The application of rattan in making table lamps is found on the hood which uses rattan material with a four-axis rattan weaving technique. This technique Arrange the woven material in 4 different directions and will produce a woven pattern with more holes with hexagonal and octagonal pattern shapes. On the lamp body is made of wood glued to the sides of the wood. So the process of making this table lamp is through material observation and experimentation. The purpose of this design is to increase consumer attractiveness to interior needs. The application of rattan material in the design of table lamps produces products that are not only aesthetically pleasing, but also pay attention to aspects of sustainability and functionality needs.